Taking back control: Minimalism as a reaction to high speed and overload in contemporary society (Sociologisk Forskning, 2019)
This paper examines the core ideas of minimalism as communicated in key writings of a selection of American bloggers and authors who have served as pacesetters for numerous people in several countries. The study examines minimalism based on narrative analysis, drawing on Hartmut Rosa’s critical theory of social acceleration and the concept of constructive resistance. The message the authors convey centres on a lifestyle change that was instigated by the discontent they felt in their previous lives, and they commend minimalism as a means to freedom and autonomy. Although critical of contemporary temporal norms and consumption culture, minimalism is primarily an individual approach to dealing with situations of discontent. This can be understood as a consequence of a more general individualization of society, but it could also be understood in relation to the unclear centre of power in the case of social acceleration. Minimalists can be seen as performing constructive resistance through individual acts without calling for organization or collective mobilization of any kind, and without being particularly challenging or threatening to the system.
Keywords: life style changes; resistance; social acceleration; tempo; time